Remarkable functions of sn-3 hydroxy and phosphocholine groups in 1,2-diacyl-sn-glycerolipids to induce clockwise (+)-helicity around the 1,2-diacyl moiety: Evidence from conformation analysis by 1H NMR spectroscopy - Nishida, Yoshihiro; Yuan, Mengfei; Fukuda, Kazuo; Fujisawa, Kaito; Dohi, Hirofumi; Uzawa, Hirotaka (Beilstein Journal of Organic Chemistry, 2017)
Cell-membrane glycerolipids exhibit a common structural backbone of asymmetric 1,2-diacyl-sn-glycerol bearing polar head groups in the sn-3 position. In this study, the possible effects of sn-3 head groups on the helical conformational property around the 1,2-diacyl moiety in the solution state were examined. 1H NMR Karplus relation studies were carried out using a series of 1,2-dipalmitoyl-sn-glycerols bearing different sn-3 substituents (namely palmitoyl, benzyl, hydrogen, and phosphates). The 1H NMR analysis indicated that the helical property around the 1,2-diacyl moiety is considerably affected by these sn-3 substituents. The sn-3 hydroxy group induced a unique helical property, which was considerably dependent on the solvents used. In CDCl3 solution, three staggered conformers, namely gt(+), gg(−) and tg, were randomized, while in more polar solvents, the gt(+) conformer with (+)-helicity was amplified at the expense of gg(−) and tg conformers. The sn-3 phosphocholine in phosphatidylcholine exhibited a greater effect on the gt(+) conformer, which was independent of the solvents used. From the 1H NMR analysis, the helical conformational properties around the 1,2-diacyl moiety conformed to a simple empirical rule, which permitted the proposal of a conformational diagram for 1,2-dipalmitoyl-sn-glycerols in the solution states.
Keywords: cell membrane; chirality; conformation; deuterium labeling; sn-glycerol; glycerolipids; glycerophospholipids; helicity; Karplus equation; proton NMR spectroscopy; staggered conformers

Cell membrane (Nature Education;)

“Glycerophospholipids” (Farooqui, A. A.;)

(untitled) - van Meer, G.; Voelker, D. R.; Feigenson, G. W. (Nat. Rev. Mol. Cell Biol., 2008)

Nomenclature of Lipids (IUPAC-IUB Commission on Biochemical Nomenclature (CBN);)

(untitled) - Bangham, A. D.; Horne, R. W. (J. Mol. Biol., 1964)

(untitled) - Singer, S. J.; Nicolson, G. L. (Science, 1972)

(untitled) - Hauser, H.; Pascher, I.; Pearson, R. H.; Sundell, S. (Biochim. Biophys. Acta, 1981)

(untitled) - Bruzik, K.; Jiang, R. T.; Tsai, M. D. (Biochemistry, 1983)

(untitled) - Plückthun, A.; DeBony, J.; Fanni, T.; Dennis, E. A. (Biochim. Biophys. Acta, 1986)

(untitled) - Hauser, H.; Pascher, I.; Sundell, S. (Biochemistry, 1988)

(untitled) - Meulendijks, G. H. W. M.; de Haan, J. W.; van Genderen, M. H. P.; Buck, H. M. (Eur. J. Biochem., 1989)

(untitled) - Goto, M.; Kodali, D. R.; Small, D. M.; Honda, K.; Kozawa, K.; Uchida, T. (Proc. Natl. Acad. Sci. U. S. A., 1992)

(untitled) - Hong, M.; Schmidt-Rohr, K.; Zimmermann, H. (Biochemistry, 1996)

(untitled) - Feller, S. E.; MacKerell, A. D., Jr (J. Phys. Chem. B, 2000)

(untitled) - Krishnamurty, S.; Stefanov, M.; Mineva, T.; Begu, S.; Devoissell, J. M.; Goursot, A.; Zhu, R.; Salahub, D. R. (J. Phys. Chem. B, 2008)

(untitled) - Nishida, Y.; Shingu, Y.; Mengfei, Y.; Fukuda, K.; Dohi, H.; Matsuda, S.; Matsuda, K. (Beilstein J. Org. Chem., 2012)

(untitled) - Uzawa, H.; Nishida, Y.; Ohrui, H.; Meguro, H. (J. Org. Chem., 1990)

(untitled) - Yuan, M.; Fukuda, K.; Dohi, H.; Uzawa, H.; Nishida, Y. (Tetrahedron: Asymmetry, 2015)

Circular Dichroic Spectroscopy Exciton Coupling in Organic Stereochemistry - Harada, N.; Nakanishi, K. (University Science Books, 1983)

(untitled) - Carrol, J. D. (Chirality, 2009)

(untitled) - Mannock, D. A.; Harper, P. E.; Gruner, S. M.; McElhaney, R. N. (Chem. Phys. Lipids, 2001)

(untitled) - Nishida, Y.; Hori, H.; Ohrui, H.; Meguro, H. (J. Carbohydr. Chem., 1988)

(untitled) - Nishida, Y.; Uzawa, H.; Hanada, S.; Ohrui, H.; Meguro, H. (Agric. Biol. Chem., 1989)

(untitled) - Uzawa, H.; Nishida, Y.; Hanada, S.; Ohrui, H.; Meguro, H. (Chem. Commun., 1989)

(untitled) - Nishizuka, Y. (Nature (London), 1984)

(untitled) - Goñi, F. M.; Alonso, A. (Prog. Lipid Res., 1999)

(untitled) - Coleman, R. A.; Lee, D. P. (Prog. Lipid Res., 2004)

(untitled) - Carrasco, S.; Mérida, I. (Trends Biochem. Sci., 2007)

(untitled) - Vilcheze, C.; Bittman, R. (J. Lipid Res., 1994)

(untitled) - Hamilton, J. A.; Bhamidipati, S. P.; Kodali, D. R.; Small, D. M. (J. Biol. Chem., 1991)

Spectral Database for Organic Chemistry (SDBS), Index No. 16108HSP-45-792

(untitled) - Holopainen, J. H.; Lehtonen, J. Y. A.; Kinnunen, P. K. J. (Biophys. J., 1999)

(untitled) - Samonshina, N. M.; Liu, X.; Brazdova, B.; Franz, A. H.; Samoshin, V. V.; Guo, X. (Pharmaceutics, 2011)

(untitled) - Hishikawa, D.; Hashidate, T.; Shimizu, T.; Shindou, H. (J. Lipid Res., 2014)

Phosphatidylcholine (Christie, W.;)
in the AOCS Lipid Library.

(untitled) - Ghosh, M. C.; Ray, A. K. (PLoS One, 2013)

(untitled) - Jang, H.-H.; Kim, D.-H.; Ahn, T.; Yun, C.-H. (Arch. Biochem. Biophys., 2010)

(untitled) - Goñi, F. M. (Biochim. Biophys. Acta, 2014)

(untitled) - Lingwood, D.; Simons, K. (Science, 2010)

(untitled) - Haasnoot, C. A. G.; de Leeuw, F. A. A. M.; Altona, C. (Tetrahedron, 1980)